Carotid geometry is independently associated with complicated carotid artery plaques - Strecker, Christoph; Kopczak, Anna; Saam, Tobias; Sepp, Dominik; Hennemuth, Anja; Mayerhofer, Ernst; Poli, Sven; Ziemann, Ulf; Poppert, Holger; Schindler, Andreas; Harloff, Andreas (Frontiers in Cardiovascular Medicine, 2023)
Introduction: Complicated carotid artery plaques (cCAP) are associated with an increased risk of rupture and subsequent stroke. Geometry of the carotid bifurcation determines the distribution of local hemodynamics and could thus contribute to the development and composition of these plaques. Therefore, we studied the role of carotid bifurcation geometry on the presence of cCAP. Methods: We investigated the association of individual vessel geometry with carotid artery plaque types in the Carotid Plaque Imaging in Acute Stroke (CAPIAS) study. After exclusion of arteries without plaque or with insufficient MRI quality, 354 carotid arteries from 182 patients were analyzed. Individual parameters of carotid geometry (i.e., internal carotid artery [ICA]/common carotid artery [CCA]-ratio, bifurcation angle and tortuosity) were derived from time-of-flight MR images. The lesion types of carotid artery plaques were determined according to the American Heart Association lesion type classification by multi-contrast 3T-MRI. Association of carotid geometry and cCAP was studied using logistic regression adjusting for age, sex, wall area and cardiovascular risk factors. Results: Low ICA/CCA-ratio (OR per SD increase 0.60 [95%-CI: 0.42-0.85]; p=0.004) and low bifurcation angle (OR 0.61 [95%-CI: 0.42-0.90]; p=0.012) were significantly associated with presence of cCAP after adjustment for age, sex, cardiovascular risk factors and wall area. Tortuosity had no significant association with cCAP. Only ICA/CCA-ratio remained significant in a model containing all three geometric parameters (OR per SD increase 0.65 [95%-CI: 0.45-0.94]; p=0.023). Conclusions: A steep tapering of the ICA relative to the CCA and, to a lesser extent, a low angle of the carotid bifurcation were associated with presence of cCAP. Our findings highlight the contribution of bifurcation geometry to plaque vulnerability. Thus, assessment of carotid geometry could be helpful to identify patients at risk of cCAP.